2000
DOI: 10.1103/physreva.63.013802
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Raman sideband generation in a coherent atomic medium

Abstract: We demonstrate the efficient generation of Raman sidebands in a medium coherently prepared in a dark state by continuous-wave low-intensity laser radiation. Our experiment is performed in sodium vapor excited in Λ configuration on the D1 line by two laser fields of resonant frequencies ω1 and ω2, and probed by a third field ω3. First-order sidebands for frequencies ω1, ω2 and up to the third-order sidebands for frequency ω3 are observed. The generation starts at a power as low as 10 microwatt for each input fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…3(a): As ω 1 and ω 2 propagate, more and more lower noise frequencies ω become correlated, and ∆S 12 (τ ) exponentially decreases and asymptotically approaches the limit set by Γ. The curve ∆S 12 (τ ) was fitted by an exponential decay function yielding a dark state coherence decay rate Γ = 0.3(1)M Hz, which is in good agreement with measurements of Γ [14] made independently of the present experiment. Additionally measurements of ∆S 12 (τ ) at 8MHz Raman detuning show, that outside the EIT regime there is no correlation effect at all!…”
supporting
confidence: 87%
“…3(a): As ω 1 and ω 2 propagate, more and more lower noise frequencies ω become correlated, and ∆S 12 (τ ) exponentially decreases and asymptotically approaches the limit set by Γ. The curve ∆S 12 (τ ) was fitted by an exponential decay function yielding a dark state coherence decay rate Γ = 0.3(1)M Hz, which is in good agreement with measurements of Γ [14] made independently of the present experiment. Additionally measurements of ∆S 12 (τ ) at 8MHz Raman detuning show, that outside the EIT regime there is no correlation effect at all!…”
supporting
confidence: 87%
“…The phase-dependent nature of EIT in such excitation systems has applications in e cient frequency conversion [27], use of theoretically predicted phase matching [26] for laser phase locking or amplitude and phase¯uctuation correlation, selective photoexcitation of molecules [28], or development of novel e cient optoelectronic devices like coherent switches, amplitude, phase and frequency modulators, wavelength converters, etc.…”
Section: Resultsmentioning
confidence: 99%
“…In a strongly driven two-level atomic system, FWM can be enhanced by the ac-Stark effect as shown in [9,10], while in an alkali atomic vapour, it can be further enhanced in the vicinity of a Raman transition. Previous studies have demonstrated that light-induced coherence between groundstate sublevels, which is responsible for the effects of coherent population trapping (CPT) [11] and electromagnetically induced transparency (EIT) [12], may facilitate the generation of new optical components detuned from the applied radiation by the ground-state splitting [13][14][15]. It was shown that light propagation in EIT atomic media with a double-level configuration is affected by resonant FWM [16].…”
Section: Introductionmentioning
confidence: 99%